Rett syndrome (MECP2) and succinic semialdehyde dehydrogenase (ALDH5A1) deficiency in a developmentally delayed female. Issue 5 (4th March 2019) - Brown, Madalyn; Ashcraft, Paula; Arning, Erland; Bottiglieri, Teodoro; McClintock, William; Giancola, Frank; Lieberman, David; Hauser, Natalie S.; Miller, Rebecca; Roullet, Jean‐Baptiste; Pearl, Phillip; Gibson, K. Michael
Abstract: Background: We present a patient with Rett syndrome (RTT; MECP2 ) and autosomal‐recessive succinic semialdehyde dehydrogenase deficiency (SSADHD; ALDH5A1 (aldehyde dehydrogenase 5a1 = SSADH), in whom the current phenotype exhibits features of SSADHD (hypotonia, global developmental delay) and RTT (hand stereotypies, gait anomalies). Methods: γ‐Hydroxybutyric acid (GHB) was quantified by UPLC‐tandem mass spectrometry, while mutation analysis followed standard methodology of whole‐exome sequencing. Results: The biochemical hallmark of SSADHD, GHB was increased in the proband's dried bloodspot (DBS; 673 µM; previous SSADHD DBSs ( n  = 7), range 124–4851 µM); control range ( n  = 2, 831), 0–78 µM. The proband was compound heterozygous for pathogenic ALDH5A1 mutations (p.(Asn418IlefsTer39); maternal; p.(Gly409Asp); paternal) and a de novo RTT nonsense mutation in MECP2 (p.Arg255*). Conclusion: The major inhibitory neurotransmitter, γ‐aminobutyric acid (GABA), is increased in SSADHD but normal in RTT, although there are likely regional changes in GABA receptor distribution. GABAergic anomalies occur in both disorders, each featuring an autism spectrum phenotype. What effect the SSADHD biochemical anomalies (elevated GABA, GHB) might play in the neurodevelopmental/epileptic phenotype of our patient is currently unknown. Abstract : A patient with combined Rett syndrome and succinic semialdehyde dehydrogenase deficiency is presented. Both disorders feature prominently on the autism spectrum continuum, with disordered GABAergic activity in the central nervous system. This report is instructive in that features of one or the other disorder could raise suspicion for additional diagnoses.